1997
DOI: 10.1074/jbc.272.50.31427
|View full text |Cite
|
Sign up to set email alerts
|

Two NFAT Transcription Factor Binding Sites Participate in the Regulation of CD95 (Fas) Ligand Expression in Activated Human T Cells

Abstract: Antigen receptor engagement on T lymphocytes activates transcription factors important for stimulating cytokine gene expression. This is critical for clonal expansion of antigen-specific T cells and propagation of immune responses. Additionally, under some conditions antigen receptor stimulation initiates apoptosis of T lymphocytes through the induced expression of CD95 ligand and its receptor. Here we demonstrate that the transcription factor, NFAT, which is critical for the inducible expression of many cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
232
1
7

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(255 citation statements)
references
References 46 publications
15
232
1
7
Order By: Relevance
“…This may be due to complex regulation of FasL transcription. The major positive regulators controlling FasL transcription are NFAT, AP-1, Egr2/3, c-Myc and NF-jB, among which only the activation of NF-jB p50 has been shown to be defective in SAP -/-CD4 + T cells, whereas NFAT and AP-1 activation are normal [52][53][54][55]. Thus, it is unlikely that FasL induction in SAP -/-CD8 + T cells will be significantly lower than that in WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to complex regulation of FasL transcription. The major positive regulators controlling FasL transcription are NFAT, AP-1, Egr2/3, c-Myc and NF-jB, among which only the activation of NF-jB p50 has been shown to be defective in SAP -/-CD4 + T cells, whereas NFAT and AP-1 activation are normal [52][53][54][55]. Thus, it is unlikely that FasL induction in SAP -/-CD8 + T cells will be significantly lower than that in WT cells.…”
Section: Discussionmentioning
confidence: 99%
“…This segment of the promoter extends in a 5Ј direction from the translational start site and encompasses all previously identified response elements (15)(16)(17)(18)(19)(20)(21)(22)(23). In the present study we have used this strain, designated CD95LP-Luc, to examine the regulation of CD95L promoter induction of luciferase activity (CD95L/luciferase) in a variety of primary murine T cell populations.…”
mentioning
confidence: 99%
“…Using the Jurkat T cell line as a model system, we and others have demonstrated a role for NF-AT in mediating transcriptional activation of the CD95L promoter (15)(16)(17)(18). Other transcription factors, such as NF-B, Sp1, and Egr-2 and -3, also contribute to inducible CD95L promoter activity (19 -22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…direct binding site for Nur77 (NBRE or NurRE) was not found in the promoter of FasL (34) indicating that the Nur77 may activate FasL by an indirect mechanism. Instead, the nuclear factors of activated T-cells (NFATs) directly binds an enhancer sequence on FasL promoter that plays a key role on the expression of FasL (36,37). Recently Lara-Pezzi et al (35) showed that HBx induced the dephosphorylation of the nuclear factor of activated T cells (NFAT), which caused translocation and transcriptional activation of the protein through a CsA-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%